Instructions to authors on generative AI in accounting publishing: Bibliometric and thematic insights - Seedwell T.M. Sithole; Syed Fahad Ashraf (European Scientific Journal, ESJ, 2025)
This study investigates how accounting journals listed in the Australian Business Deans Council (ABDC) Journal Quality List address the use of generative artificial intelligence (AI) tools in scholarly publishing. Ninety-one A*, A, and B-ranked journals classified under Accounting (FoR 3501) were examined through a structured bibliometric review and thematic content analysis of author guidelines. The analysis revealed considerable variation in journal policies concerning AI use. While some journals provided clear disclosure requirements, others offered limited or no guidance, resulting in inconsistent expectations across the discipline. This lack of standardisation poses challenges for authors, editors, and institutions striving to uphold responsible research practices. The findings underscore the need for coherent, discipline-specific guidelines that ensure the ethical and transparent use of AI in accounting research. In response, the study proposes a framework for AI governance tailored to the accounting field. The framework includes standardised disclosure protocols, procedures for evaluating potential misuse, and the incorporation of AI ethics into journal practices. Aligning academic publishing standards with principles of transparency, accountability, fairness, and integrity, this research contributes to the development of best practices for managing AI use in accounting scholarship and informs broader discussions on responsible AI governance within academic and professional contexts.